The use of games for improving the speaking skill of the english language with 6th year students of basic education in parallel C at Zoila Alvarado de Jaramillo school, academic period 2013-2014 - Agila Salazar, Javier Mauricio (2015)
This action research study was focused on the improvement of the pronunciation skill with the use of songs of 29 fourth-B year students at “Zoila Alvarado de Jaramillo” public school. Eight sessions were carried out to improve the skill using English children songs. Researcher’s-made tests and questionnaires were used to measure the students’ progress and perception of the songs use and the pronunciation. Field diaries were also used in every session to observe and record the students’ growth. The results indicated that the use of songs facilitated meaningfully the improvement of pronunciation skill which was reflected in the noticeable increase of the posttest scores and students’ progress during the intervention.